Intishar Dzahirah al-Talaq fi al-Mujtama’ al-Libiy - Ezbeyda, Hamed Abdelsalam Mansour; Isniba, Abdallah Elsharif Ahmed (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2024)
Abstract: This study aimed to describe and analyze the proliferation problem in Libyan society. To achieve this goal, the researcher resorted to descriptive analysis and, through his knowledge of some of the problems between divorced men and women and their families. It became clear from the analysis of current facts that going out on a group that desires the general social that society relies on in its relationships and connections is a reason for shaking the foundations of Brazilian relations between spouses to distance their specialization and others that support it, such as the comprehensive political situation, diversity, tribal traditions and the transformations that society is going through as a result. [1]These factors, as the problems that affect consumers in society, are of a value nature, coordination between values ​​in society and what it includes of ideas, values, customs and traditions about marriage, the relationship between spouses, the characteristics and special medicine of both of them and the intervention of the family, we seek or positively like the course of the various relationships between them. The study concluded that there is nothing wrong with that and added the efforts of society from its individuals and its social and religious educational bodies objectively to address this problem and end it. Also, conducting a management study by specialists involves participating in its issues and circumstances and identifying its various social contexts to establish its necessity. Keywords: divorce, Islam, fiqh, society. الملخص: هدفت هذه الدراسة إلى وصف مشكلة ظاهرة انتشار الطلاق وتحليلها في المجتمع الليبي وفي سبيل تحقيق هذا الهدف عمد الباحث إلى المنهج التحليلي الوصفي ومن خلال اطلاعه على بعض القضايا التي تحدث بين المطلقين والمطلقات وأسرهم . وتبين من تحليل الوقائع أن الخروج على مجموعة المعايير الاجتماعية والثقافية والاقتصادية التي يستند إليها المجتمع في علاقاته وارتباطاته سبب في زعزعة أسس العلاقات العاطفية بين الزوجين بفعل عوامل داخلية تخصهما وأخرى مساندة لها مثل الوضع السياسي والاجتماعي والاقتصادي والأعراف والتقاليد القبلية والتحولات التي يمر بها المجتمع .نتيجة تلك العوامل ، إذ إن المشكلات الأسرية المنتشرة في المجتمع هي ذات طبيعة قيمية ، فالنسق القيمي في المجتمع وما يتضمنه من أفكار وقيم وعادات وتقاليد عن الزواج ، والعلاقة بين الزوجين، والصفات والطبائع الخاصة لكليهما وتدخل الأهل تؤثر سلباً أو إيجاباً في طبيعة سير العلاقة بينهما وبين المجتمع. وانتهت الدراسة إلى أنَّه لا بد من تدخل وتضافر جهود المجتمع بأفراده ومؤسساته وهيئاته الاجتماعية والدينية والقانونية بموضوعية لمعالجة هذه المشكلة ووضع حد لها ؛ وكذلك القيام بدراسة تاريخية من قبل مختصين يتم فيها توثيق وقائعه وحيثياته وتحديد السياقات الاجتماعية والثقافية المرتبطة به لكي يتسنى وضع العلاج اللازم لها. الكلمات المفتاحية: الطلاق، الاسلام، الفقه، المجتمع. [1]